Rodzina chrześcijańska jako wspólnota wiary i ewangelizacji w nauczaniu papieża Franciszka - Celary, Ireneusz (Studia Pastoralne, 2026)
In his teaching Pope Francis often emphasizes that the most important duty of the Church is preaching the Gospel. Its proclamation is a sign of maturity of the Church community. However in many situations it should have missionary character. Francis reports that in a secularized world all baptized people are called to give the testimony of faith. He believes that people learn the Gospel within families first and then they would proclaim it to the world. Pope Francis perceives the family as an environment of faith and evangelization. He indicates that raising awareness of Church in this aspect is confronted – especially in the western cultural and social context – with attacks against families which can fulfill their duties facing difficulties. This aspect is raised in the first part of the article. In the second part, on the social and cultural background teaching of Pope Francis about the role of family as a community of faith and evangelization is presented.